A Single-Mode Erbium Fiber Laser With Flat Power Output and Wide Wavelength Tunability - Chien-Hung Yeh; Wei-Yao You; Jhao-Ren Chen; Wen-Piao Lin; Chi-Wai Chow; Jing-Heng Chen (IEEE Photonics Journal, 2020)
In this research, we present and study an erbium fiber laser with triple-fiber-ring (TFR) scheme for continuous-wave (CW) wavelength-selection. The designed TFR not only can achieve single-longitudinal-mode (SLM) oscillation, but also can spread the tuning range from 1519.0 to 1583.0 nm covering C- and part of L-bands. Moreover, 0 dB power fluctuation can be obtained from 1523.0 nm to 1559.0 nm for flattened operation based on the compound-ring configuration. The Lorentzian laser linewidths of 22 to 29 kHz are also attained in the entire wavelength-tunable range.